2015
DOI: 10.1089/omi.2014.0164
|View full text |Cite
|
Sign up to set email alerts
|

Combined Metabolomics and Proteomics Analysis of Major Depression in an Animal Model: Perturbed Energy Metabolism in the Chronic Mild Stressed Rat Cerebellum

Abstract: Major depressive disorder (MDD) is a highly prevalent, debilitating mental illness of importance for global health. However, its molecular pathophysiology remains poorly understood. Combined proteomics and metabolomics approaches should provide a comprehensive understanding of MDD's etiology. The present study reports novel ''-omics'' insights from a rodent model of MDD. Cerebellar samples from chronic mild stressed (CMS)-treated depressed rats and controls were compared with a focus on the differentially expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 83 publications
(51 citation statements)
references
References 69 publications
3
48
0
Order By: Relevance
“…21,22 Based on metabolomics technology, our previous studies found both a disturbance in energy metabolism in the cerebellum and a dysfunction of amino acid and lipid metabolism in the hippocampus of CUMS model rats. 23,24 These preliminary findings suggest that depression involves metabolic alterations in multiple brain regions. However, previous studies have mostly focused on a single brain region, thus ignoring the systemic metabolic alterations that occur in multiple brain regions during the pathology of depression.…”
Section: Introductionmentioning
confidence: 79%
“…21,22 Based on metabolomics technology, our previous studies found both a disturbance in energy metabolism in the cerebellum and a dysfunction of amino acid and lipid metabolism in the hippocampus of CUMS model rats. 23,24 These preliminary findings suggest that depression involves metabolic alterations in multiple brain regions. However, previous studies have mostly focused on a single brain region, thus ignoring the systemic metabolic alterations that occur in multiple brain regions during the pathology of depression.…”
Section: Introductionmentioning
confidence: 79%
“…Currently, metabolomics and other methods have been developed to identify the potential biomarkers for neuropsychiatric disorders,13,14 including depression, bipolar disorder and schizophrenia 1517. Through metabolomics, previous studies found that there were urinary metabolic abnormalities in patients with MDD 15,18.…”
Section: Introductionmentioning
confidence: 99%
“…Adenylate kinase 1 maintains the balance between ATP consumption and production by catalyzing the reversible phosphotransfer between ADP, ATP and AMP [30]. A literature search indicated that energy metabolism-related proteins were decreased in positively stimulating conditions, while they increased in stressful conditions or mental disorders [31,32,33,34]. In support of our results, two interesting studies showed that a lower level of brain activation was observed in EE animals following an anxiety-inducing task [35,36].…”
Section: Discussionmentioning
confidence: 99%